Increased sialylation of site specific O-glycoforms of hemopexin in liver disease. Issue 1 (December 2016) - Sanda, Miloslav; Benicky, Julius; Wu, Jing; Wang, Yiwen; Makambi, Kepher; Ahn, Jaeil; Smith, Coleman; Zhao, Peng; Zhang, Lihua; Goldman, Radoslav
Abstract Background Non-invasive monitoring of liver disease remains an important health issue. Liver secreted glycoproteins reflect pathophysiological states of the organ and represent a rational target for serologic monitoring. In this study, we describe sialylated O-glycoforms of liver-secreted hemopexin (HPX) and quantify them as a ratio of disialylated to monosialylated form (S-HPX). Methods We measured S-HPX in serum of participants of the HALT-C trial using a LC–MS/MS-MRM assay. Results Repeated measurements of S-HPX in the samples of 23 disease-free controls, collected at four different time points, show that the ratio remains stable in the healthy controls but increases with the progression of liver disease. The results of measurement of S-HPX in serum of participants of the HALT-C trial show that it increased significantly (Kruskal–Wallis test, p < 0.01) in liver disease as the stage of fibrosis progressed in liver biopsies. We observed a 1.7-fold increase in fibrosis defined as Ishak score 3–4 (24.9 + 14.2, n = 22) and 4.7-fold increase in cirrhosis defined as Ishak score 5–6 (68.6 + 38.5; n = 24) compared to disease-free controls (14.7 + 6.7, n = 23). S-HPX is correlated with AFP, bilirubin, INR, ALT, and AST while inversely correlated with platelet count and albumin. In an independent verification set of samples, S-HPX separated the Ishak 5–6 (n = 15) from the Ishak 3–4 (n = 15) participants with AuROC 0.84; at the same time, the Ishak 3–4 group was separated from disease-free controls (n = 15) with AuROC 0.82. Conclusion S-HPX, a measure of sialylated O-glycoforms of hemopexin, progressively increases in fibrotic and cirrhotic patient of HCV etiology and can be quantified by an LC–MS/MS-MRM assay in unfractionated serum of patients. Quantification of sialylated O-glycoforms of this liver secreted glycoprotein represents a novel measure of the stage of liver disease that could have a role in monitoring the progression of liver pathology.